A Solution of Airy Differential Equation Via Elzaki Transform - Kumar, Nand Kishor; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2025)
The Elzaki transform provides an elegant method to solve the Airy differential equation, leveraging its unique properties to handle the mixed derivative and variable coefficient terms. While the traditional methods remain standard, the Elzaki transform offers a powerful alternative, particularly when coupled with numerical techniques.